Development of hydrophobic reduced graphene oxide as a new efficient approach for photochemotherapy - Mousavi S.M.; Low F.W.; Hashemi S.A.; Samsudin N.A.; Shakeri M.; Yusoff Y.; Rahsepar M.; Lai C.W.; Babapoor A.; Soroshnia S.; Goh S.M.; Tiong S.K.; et al. (Royal Society of Chemistry, 2023)
Biocompatibility; Biomedical engineering; Cell death; Chemotherapy; Disintegration; Infrared devices; Reduced Graphene Oxide; Absence of cells; Clinical settings; Medical technologies; Membrane disruption; Near infrared region; Phosphatidylserine; Photochemotherapy; Reduced graphene oxides (RGO); Graphene